PENGARUH PENGGUNAAN BAHAN AJAR BROSUR TERHADAP PENGUASAAN MATERI OLEH SISWA - Soni Satrian Syah; Tri Jalmo; Berti Yolida (Universitas Lampung, 2015)
This research was aimed to know the influence of brochure learning material towards students learning result and students learning activities. The design of this research was pretest and protest with non-equivalent. The subjects of this research were students inthe class X2 dan X3 of SMAN 1 Sukadana, chosen by purposive sampling. The quantitative data were the learning result that were analyzed by using T-Test and U-Test. The qualitative data were the observation sheet of learning activities and student reaction that were analyzed descriptively. Students achievement in experiment class was significantly different by average N-Gain 65,79. The indicator of C1 and C2 questions showed the significantly result. The average of student learning activities in the aspect of askingquestions (25.78 %), giving opinions (39.84%), communication (85.94%), cooperating (90.63%), and the answering questions (75.78%). Thus, brochure learning material could increase students learning result and students learning activities on the subject matter of Animalia kingdom.Penelitian ini bertujuan mengetahui pengaruh bahan ajar brosur terhadap hasil belajar dan aktivitas siswa. Desain yang digunakan yaitu pretes-postes tak ekuivalen. Subjek penelitian adalah siswa kelas X2 dan X3 SMAN 1 Sukadana yang dipilih secara purposive sampling. Data kuantitatif berupa hasil belajar yang dianalisis meng-gunakan uji T dan uji U. Data kualitatif berupa aktivitas belajar dan tanggapan siswa yang dianalisis secara deskriptif. Hasil belajar siswa pada kelas eksperimen berbeda signifikan dengan rata-rata N-gain 65,79. Dan data indikator soal C1 dan C2 menunjukkan hasil berbeda signifikan. Rata-rata aktivitas belajar siswa pada aspek mengajukan pertanyaan (25,78%), memberikan pendapat (39,84%), berkomunikasi (85,94%), bekerjasama (90,63%), dan men-jawab pertanyaan (75,78%). Sehingga, penggunaan bahan ajar brosur dapat me-ningkatkan hasil belajar dan aktivitas siswa pada materi pokok dunia hewan.Kata kunci : brosur, dunia hewan, hasil belajar siswa, model TPS